PENGARUH WORD OF MOUTH MARKETING DALAM PENCIPTAAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN MOBIL WULING AIR EV - Andini Septia Ningrum; Ainun Mardhiyah; Onan Marakali Siregar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The growth of environmentally friendly vehicles in Indonesia has intensifiedcompetition in the electric vehicle industry, including the emergence of the WulingAir EV as one of the most popular electric cars among consumers. Although itrecorded the highest electric vehicle sales in 2022, Wuling Air EV experienced adecline in sales in subsequent years. This condition indicates challenges inmaintaining consumer interest amid increasingly competitive market conditions.This study aims to analyze the influence of Word of Mouth Marketing on BrandImage and Purchase Decisions, as well as to examine the role of Brand Image ininfluencing consumers’ Purchase Decisions of Wuling Air EV cars in Medan City.This research employed a quantitative descriptive approach using purposivesampling techniques. The sample consisted of 100 Wuling Air EV users in MedanCity. Primary data were collected through questionnaires distributed directly and viaGoogle Forms, while secondary data were obtained through literature studies. Dataanalysis was conducted using Structural Equation Modeling–Partial Least Square(SEM-PLS). The results indicate that Word of Mouth Marketing has a positive andsignificant effect on Purchase Decisions, with a t-statistic value of 1.803 and a pvalue of 0.036. However, Word of Mouth Marketing does not have a significant effecton Brand Image, with a t-statistic value of 0.851 and a p-value of 0.197. Meanwhile,Brand Image has a positive and highly significant effect on Purchase Decisions, witha t-statistic value of 29.845 and a p-value of 0.000. The R² value of 0.810demonstrates that the model has strong explanatory power in explaining PurchaseDecisions, while the Q² value of 0.512 indicates good predictive relevance.